Mind the gap: flow recession mortality of the river mussel Alathyria jacksoni revealed from acoustic detection gaps - Jerom R. Stocks; Stephanie L. McCaffrey (Animal Biotelemetry)
Abstract Background The utility of nondetection data in freshwater ecosystems for sessile species is often overlooked in aquatic ecological monitoring although can be particularly informative when interpreted in the right context. The aim of this study was to investigate a novel approach of using nondetection of acoustic telemetry data to identify strandings and mortality of the river mussel Alathyria jacksoni associated with flow recession in a regulated river of the Australian Murray–Darling Basin. Acoustic transmitters were externally attached to A. jacksoni and continuously monitored by an array of acoustic receivers for 200 days. Results Acoustic signal presence/absence data, knowledge of abiotic conditions and the species desiccation tolerances were used to infer the timing of a mortality event, with ground surveys validating the inference. Mortality of 50%, of the tagged mussels was inferred from strandings during a period of water level recession combined with extended low river discharge and high air temperatures. Conclusion This study highlights the utility of acoustic detection gaps in ecological research on sessile invertebrates. It provides a successful proof-of-concept for identifying the timing of stranding-induced mortality events, demonstrated using a small sample of the freshwater river mussel Alathyria jacksoni. The findings illustrate how similar approaches could inform future water management in regulated river systems to support the recovery of threatened Unionida populations worldwide.